Monte Carlo simulation of radiation beam of cobalt 60 source in reference conditions - Vargas-Segura, Walter (2023)
The purpose of this study is to generate the simulation and validation of a cobalt 60 beam of a radiotherapy equipment under reference conditions, using evaluation parameters corresponding to commercial planning systems. For this, we used dose profile and percentage depth dose (PDD) data for a field size of 10 cm x 10 cm at a surface source distance (DFS) of 80 cm from the water phantom. The program used to simulate the radiation beam was Geant4, including a collimation system and the phantom. When comparing the simulation results with the measured data, a difference of 3.50 % was obtained in the region defined between the maximum dose and 50 % in the PDD curve, as well as a maximum deviation of 0.96 mm in buildup region in the PDD. In addition, there is a deviation of 1.42 mm in the penumbra region for the dose profile. For the zone outside the central axis in the dose profile and in the zone of low doses, they were 2.41 % and 2.56 %, respectively. Based on the results obtained, this paper validates the simulated conditions.